Potentials of waste and wastewater resources recovery and re-use (RRR) options for improving water, energy and nutrition security - Maksud Bekchanov (University of Bonn, Center for Development Research (ZEF), 2017)
Under increasing demand for water, fertilizer and energy, waste and wastewater treatment can be potential options for considerably enhancing not only the supply of these valuable economic assets but also for improving sanitation and ecological conditions. Effluents and treated wastewater are important for meeting water demands for agricultural irrigation, landscape irrigation, and environmental system enhancement. Fertilizer and nutrients recovered though recycling organic waste and filtering wastewater, or embedded in effluents can be essential inputs for increasing crop biomass, timber output, and production of aquatic crops and marine species such as fish. Similarly, energy recovered from waste and wastewater recycling (including dry manure for cooking and heating) is important for enhanced energy supply especially in remote rural areas of the developing countries. Yet, the utilization of the waste and wastewater resources for additional gains should consider the accepted safety measures in order to prevent environmental and health risks. Focusing on potential benefits from resources recycling and recovery yet being cautious on their external effects, this review critically assesses the available waste and wastewater treatment options, and their economic, environmental and health benefits and risks.
Keywords: 330; waste; wastewater; effluents; nutrients and energy recovery